UK outlook: Fallout - Ben Nabarro (Institute for Fiscal Studies (IFS), 2023)
The UK economy remains stuck between weak growth on the one hand and the risk of persistently high inflation on the other.
Keywords: 330; Government finances and spending; IFS Green Budget 2023; Government spending; Business and investment; IFS Green Budget 2023; Inflation; Fiscal performance